Exceptional synergistic response of PARP inhibitor and immune checkpoint inhibitor in esophageal adenocarcinoma with a germline BRCA2 mutation: a case report - Himil Mahadevia; Ben Ponvilawan; Ammar Al-Obaidi; Jennifer Buckley; Janakiraman Subramanian; Dhruv Bansal (Therapeutic Advances in Medical Oncology, 2024)
Immune checkpoint inhibitors (ICIs) and poly (ADP-ribose) polymerase (PARP) inhibitors have shown efficacy in various tumors. A significant therapeutic challenge with either ICIs or PARP inhibitors as monotherapy is treatment failure from intrinsic primary resistance or the development of secondarily acquired resistance after a period of responsiveness. The combination of PARP inhibitors and ICIs could mitigate this by potentiating treatment response. We describe an 83-year-old male patient who initially presented with abdominal pain, and weight loss along with alternating constipation and diarrhea. Imaging and biopsy revealed metastatic esophageal adenocarcinoma. Genomic testing revealed germline BRCA2 mutation. The patient initially underwent a few cycles of chemoimmunotherapy. However, due to intolerance to chemotherapy, the patient’s case was discussed at a multidisciplinary molecular tumor board. He was switched to PARP inhibitor olaparib and ICI nivolumab. This combination led to a durable complete response. A combination of poly-ADP ribose polymerase inhibitor (PARPi) plus ICI may work in synergy through various mechanisms including enhanced neoantigen expression, release of immune-activating cytokines, and increased programmed death-ligand 1 expression. This may culminate in accentuated efficacy outcomes with a manageable safety profile. This exceptional response with ICI and PARPi in our case is consistent with the synergistic value of this combination, and prospective studies are warranted to definitively characterize clinical utility.